2020
DOI: 10.1051/bioconf/20201700117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeolites on soil modification and productivity

Abstract: Local natural zeolite-containing rocks use efficiency in agriculture of the Republic of Tatarstan was studied in the research. The research was conducted in the field on leached black soil applying mechanoactivated zeolites and in greenhouses on grey forest soil using nanostructured zeolite. Field experiments identified the soil deacidification of 0.4 pHsol, increase of assimilable phosphates of the 1st and 2nd groups (Ca-P1 и Ca-P2) – of 5.0 and 6.6 mg per 100 g of soil. Moreover, the research considered the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The total numbers of reads for the control (non‐amended) soil sample and the zeolite‐amended soil sample were 37,941 and 42,936, respectively. In general, zeolite improves the retention of water and reserves of ammonium and phosphorus in soil due to its large cation exchange capacity, surface area, and porosity (Bikkinina et al, 2020), which tends to increase the total number of microorganisms in the soil (Rusyn et al, 2020). Our study indicates, however, that this increase in abundance is not associated with increased bacterial diversity.…”
Section: Resultsmentioning
confidence: 99%
“…The total numbers of reads for the control (non‐amended) soil sample and the zeolite‐amended soil sample were 37,941 and 42,936, respectively. In general, zeolite improves the retention of water and reserves of ammonium and phosphorus in soil due to its large cation exchange capacity, surface area, and porosity (Bikkinina et al, 2020), which tends to increase the total number of microorganisms in the soil (Rusyn et al, 2020). Our study indicates, however, that this increase in abundance is not associated with increased bacterial diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite incorporation can also improve nutrient retention [ 14 ] and help buffer soil pH, reducing the need for lime [ 28 ]. Bikkinina et al [ 95 ] demonstrated in a field experiment that the application of zeolites to leached black soil resulted in an increase in soil pH, plant-available phosphorus and potassium, improved microbial activity in the rhizosphere, and accelerated microbial biomass growth. Due to its alkaline nature and the presence of a negative charge, phosphorus availability is increased in zeolite-enriched soils following an increase in soil pH and a decrease in the amount of exchangeable iron and aluminum ions [ 90 , 96 ].…”
Section: Applications Of Zeolitesmentioning
confidence: 99%
“…As a result, every year, a forest area of 50,000 km 2 disappears from the face of the earth. Thus, since 2010, agriculture has already destroyed or radically transformed 70% of grasslands, 50% of savannas, 45% of temperate deciduous forests and 25% of tropical forests [18]. Against these volumes, the increase in production has been only 20% [19].…”
Section: Soil Desertification and Sustainable Use Of Fertilizersmentioning
confidence: 99%